Draft Seventh Five Year Plan 1985-90 and Draft Annual Plan 1985-86 Centrally Sponsored Schemes Union Territory of Pondicherry - Planning Commission (Planning Commission, 1985)
Only taken provision has been proposed 'for the Scheme numbers 5, 3, 7 and 10 in the absence of specific sanction from Government of India fore the operation of these schemes.
Government of Pondicherry, Planning and Research Department